Pengaruh kualitas pelayanan dan harga terhadap kepuasan pelanggan jasa transportasi Gojek di Kota Jambi - Ariyandi, Rizkon; Dahmiri, Dahmiri; Sari, Novita (Jurnal Dinamika Manajemen, 2020)
One of the transportation service companies developing in the city of Jambi is Gojek. Go-Jek is the pioneer of mobile application-based motorcycle taxi services through its Go-Ride service. The increasing number of online motorcycle taxis impacts tighter competition. The factors causing this are price competition and the many online motorcycle taxi services choices. This study aimed to determine the effect of service quality and price simultaneously and partially on customer satisfaction on GoJek transportation services in Jambi City. The approach used in this research is quantitative. The sampling technique used was through interviews, observations, and questionnaires. The data analysis technique in this study is multiple linear regression with the help of SPSS version 25.0 software. The results of this study are: (1) Service quality does not significantly affect customer satisfaction of Gojek online transportation users in Jambi city. This variable has a positive influence on customer satisfaction. (2) Price has a significant effect on customer satisfaction of Gojek online transportation users in Jambi city, and this variable has a positive influence on customer satisfaction. (3) Service quality and price perception together have a significant influence on the customer satisfaction of Gojek online transportation users in Jambi. This variable has a positive influence on customer satisfaction.Â 